Implementasi Produk Hukum Bupati Musi Rawas Nomor 26 Tahun 2023 Tentang Tata Kerja Sekretariat DPRD Kabupaten Musi Rawas - Yudistira Ferdinandus; Fransisco, Wawan; Fuadi, Ahmad (STAI Bumi Silampari, 2026)
This study aims to analyze the implementation of the Musi Rawas Regent Regulation Number 26 of 2023 concerning the organizational structure, duties, functions, and work procedures of the Secretariat of the Regional House of Representatives (DPRD) of Musi Rawas Regency, as well as to identify the factors influencing the effectiveness of its implementation. This research employs a normative-empirical legal method using a juridical-normative approach combined with field data obtained through interviews and document studies. The data were analyzed descriptively and qualitatively to examine the conformity between the applicable legal norms and their implementation within the DPRD Secretariat. The findings indicate that the implementation of the Regent Regulation has been carried out quite effectively, as reflected in the employees’ adequate understanding of the organizational structure, duties, and functions of their respective positions. In addition, human resources, the level of understanding and commitment of employees, budget support, as well as evaluation and supervision systems are the main factors influencing the effectiveness of the regulation’s implementation. The study further reveals that organizational culture and the professionalism of the apparatus play an important role in optimizing the work procedures of the DPRD Secretariat in accordance with the principles of good governance.